(untitled) (Communications in Mathematical Research, 2021)
In theoretical chemistry, the geometric-arithmetic indices were introduced to measure the stability of alkanes and the strain energy of cycloalkanes. In this note, we report the general third geometric-arithmetic index of unilateral polyomino chain and unilateral hexagonal chain. Also, the third geometric-arithmetic index of these chemical structures are presented.